1996
DOI: 10.1159/000109173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Anticancer Drugs and Combined Chemotherapy on Renal Toxicity

Abstract: The nephrotoxic action of anticancer drugs such as nitrogranulogen (NG), methotrexate (MTX), 5-fluorouracil (5-FU) and cyclophosphamide (CY) administered alone or in combination [MTX+5-FU+CY (CMF)] was evaluated in experiments on Wistar rats. After drug administration, creatinine concentrations in the plasma and in the urine of the rats were determined, as well as creatinine clearance. Histopathologic evaluation of the kidneys was also performed. After MTX administration a significant increase (p = 0.0228) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Increase in levels of malondialdehyde along with decreased levels of glutathione concentrations, after treatment with 5-FU, was also seen in renal tissues [5]. Similar results were observed in another study that showed 5-FU-induced nephrotoxicity in normal rats [6]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Increase in levels of malondialdehyde along with decreased levels of glutathione concentrations, after treatment with 5-FU, was also seen in renal tissues [5]. Similar results were observed in another study that showed 5-FU-induced nephrotoxicity in normal rats [6]. …”
Section: Discussionsupporting
confidence: 72%
“…However, this killing is nonselective and not only eliminates the fast-growing cancer cells but also other fast-growing cells in the body, including hair and blood cells, owing to which it exhibits severe toxicity and undesirable side effects [4]. 5-FU has been shown to be associated with renal toxicity [5, 6]. This puts the patient at added risk when undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies suggest that morphological changes in tubular and glomerular area after Mtx treatment. 29 Histopathological evidence of kidney injury includes degenerated and vacuolated tubules, tubular atrophy or necrosis, changes in Bowman’s space, vascular congestion, and glomerular fibrosis. At the same time, owing to the deterioration in the balance of oxidant–antioxidant mechanisms and shifting toward the oxidant status, changes in the levels of enzymes SOD and MDA can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings also reveal that 5-FU causes male reproductive organ damage by inhibiting thymidylate synthetase and by incorporation into genetic material. 11,[47][48][49] Histological analysis indicate that Tau administration attenuated the 5-FU-induced degeneration of seminiferous epithelium, vacuolization of Sertoli cells in testis and atrophy of prostatic acini, nuclear stratification, and increased secretion in prostate.…”
Section: Discussionmentioning
confidence: 99%